Live zoster vaccination in an immunocompromised patient leading to death secondary to disseminated varicella zoster virus infection. Issue 27 (22nd June 2018) - Alexander, Kate E.; Tong, Philip L.; Macartney, Kristine; Beresford, Rohan; Sheppeard, Vicky; Gupta, Monisha
Abstract: In 2016, the live attenuated zoster vaccine (Zostavax, Merck and Co, USA) was introduced into the Australian National Immunisation Program for people aged 70 years who are not significantly immunocompromised. We report the administration of Zostavax in an immunocompromised patient with chronic lymphocytic leukaemia and no evidence of primary varicella zoster virus (VZV) infection. The patient presented with a bilateral vesicular facial rash 22 days after receiving Zostavax and was initially managed as an outpatient with oral acyclovir. He re-presented three days later and was diagnosed with disseminated VZV infection complicated by meningoencephalitis. The patient died following cardiac arrest on day 10 of hospitalisation. This unfortunate case highlights the challenge of safely implementing a high titre live vaccine in a population where contraindications are prevalent. The non-live recombinant herpes zoster subunit vaccine (Shingrix, GSK) may provide a safe and effective option to protect immunocompromised patients from shingles and post-herpetic neuralgia.